Impact of Ogbomoso Journal of Theology on Developmental Works in Africa and Beyond - Oladejo, Dr Olusayo Bosun; Adetunji, Dr Adeniyi Temitope (International Journal For Research In Business, Management And Accounting, 2016)
his paper was designed to discuss the contribution of Ogbomoso Journal of Theology (OJOT) to educational developmental work and civilisation of Africans. The paper is a desk research and a review of the OJOT activities in the African continent with concentration on how missionary education contributed to human development on the continent. The study reveals that OJOT has made significant impact to developmental works through theological education and scholarly contribution in Africa and beyond, especially in the areas of poverty alleviation, holistic healing and health awareness, and prevention or reduction of societal ills through ministrations.